[Connie Nash Brady, Architectural Design, 1962]
Connie Nash Brady, Architectural Design, 1962. Photo included in Cal Poly Today article "A Tale of Cal Poly's First Four Women Architects" by Marlene Goldman, Summer 1981, which featured Joyce Dolman Vagasy (Architectural Design, 1962), Pat Dellinger Della (Architectural Engineering, 1961), and Ingeborg (Inge) Rose (Architectural Engineering, 1966).